English language at school from the point of view of students and teachers: Implications on teaching and learning - Eidelwein, Marina Hofstätter; Mottin, Lívia Pretto (BELT - Brazilian English Language Teaching Journal, 2021)
Considering English as a language that has assumed an increasingly important role in the globalized world where we live, it is necessary to assess how this language has been seen and, consequently, taught in schools. Thus, this article analyzes the views of students and teachers about the English language, as well as the didactic-methodological implications of language teaching in the classroom, based on semi-structured non-directed interviews. The interviews were carried out with English teachers and students of the third year of high school at two state public schools in Vale do Taquari, in Rio Grande do Sul, Brazil. The results show that the English language has been seen as a global lingua franca, which can be used in different communicative contexts as an additional language, bringing many benefits to speakers and, therefore, increasing interest in its learning. However, it was found that the methodology adopted in schools does not provide the necessary development of skills for this language to be put on use, which is a major factor for the demotivation of students, that see no reason to study grammar rules in a decontextualized and repetitive way. Therefore, it is indicated that the teaching of English at school needs to be focused on the development of projects based on tasks that seek to provide students with real language use situations, through which it is possible to develop linguistic competence focused on the principle of intelligibility.